2010
DOI: 10.1098/rspb.2010.0826
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic evidence that males trade attractiveness for ejaculate quality in guppies

Abstract: Polyandry, where females mate with multiple males, means that a male's reproductive success will depend both on his ability to acquire mates and the ability of his sperm to compete effectively for fertilizations. But, how do males partition their reproductive investment between these two episodes of selection? Theory predicts that increases in ejaculate investment will come at a cost to investment in other reproductive traits. Although evidence revealing such trade-offs is accumulating, we know little about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 55 publications
6
118
1
Order By: Relevance
“…The study complements recent quantitative genetic analyses of pre and postcopulatory sexually-selected traits in this species in which two measures of in vitro sperm performancesperm swimming velocity (average path velocity; VAP), and the proportion of live sperm per ejaculate (sperm viability)-were shown to be negatively genetically associated with male sexual behaviour and body ornamentation (Evans, 2010). The present study extends these analyses by exploring patterns of genetic covariation among ejaculate traits, adding to just handful of studies that have addressed this topic in other species (reviewed by Simmons and Moore, 2009).…”
Section: Introductionmentioning
confidence: 78%
“…The study complements recent quantitative genetic analyses of pre and postcopulatory sexually-selected traits in this species in which two measures of in vitro sperm performancesperm swimming velocity (average path velocity; VAP), and the proportion of live sperm per ejaculate (sperm viability)-were shown to be negatively genetically associated with male sexual behaviour and body ornamentation (Evans, 2010). The present study extends these analyses by exploring patterns of genetic covariation among ejaculate traits, adding to just handful of studies that have addressed this topic in other species (reviewed by Simmons and Moore, 2009).…”
Section: Introductionmentioning
confidence: 78%
“…Here we assume that there is no direct trade-off between sperm number and viability, but a trade-off between investment in winning fertilizations (i.e., ejaculate investment) and investment in obtaining matings (for empirical evidence see Warner et al 1995;Danielsson 2001;Evans 2010;Simmons et al 2010;Engqvist 2011). As in many previous sperm competition models (e.g., Ball and Parker 1996; Parker et al 1996Parker et al , 1997Tazzyman et al 2009), this trade-off is expressed as .…”
Section: Trade-off Between Investment In Winning Fertilizations and Imentioning
confidence: 99%
“…Alternatively, at least in some insects, sperm viability has been shown to be accomplished by seminal fluids (Holman 2009a), which may be costly to produce. Trade-offs may also be present between investment in sperm quality and other aspects of male reproductive success, such as investment in traits affecting attractiveness and mating success (Evans 2010;Simmons et al 2010;Engqvist 2011;Preston et al 2011). Yet not much is known concerning which factors may benefit sperm viability.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, both sperm number and sperm quality may increase in response to sperm competition (Locatello et al 2007) potentially forcing a trade-off with nonejaculate traits. For example, ejaculate quality may trade off with attractiveness (Evans 2010;Rowe et al 2010) or immune function (Simmons 2012), and testes size has been shown to trade off with traits such as flight capability (Saglam et al 2008) and weaponry (Simmons and Emlen 2006). It is therefore possible that increased investment in ejaculates could trade off with traits that directly enhance female fitness, such as nuptial gift size or provision of parental care (e.g., Simmons et al 1993).…”
Section: Ejaculate Variationmentioning
confidence: 99%